2015
DOI: 10.1016/j.compag.2015.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optimal irrigation scheduling and groundwater recharge at representative sites in the North China Plain with SWAP model and field experiments

Abstract: a b s t r a c tThe application of water saving irrigation is essential to alleviate the rapid depletion of groundwater resources in water crisis areas such as the North China Plain (NCP). The integrated effects of climate, soil and groundwater conditions on water balance and crop response need to be further studied. It is imperative to investigate spatial differences of irrigation scheduling and groundwater recharge within the NCP for regional water management. In this study, three representative sites includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
0
19
0
3
Order By: Relevance
“…Crop variables (LAI, crop height, and rooting depth) were specified as a function of the crop development stage. The development stage was assumed to be linear with a growth period from emergence to harvest (0 < development stage < 2) (Ma et al., ). Extinction coefficients for diffuse and direct visible light were used as the model default values, which were 0.60 and 0.75, respectively (Hassanli et al., ; Jiang et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop variables (LAI, crop height, and rooting depth) were specified as a function of the crop development stage. The development stage was assumed to be linear with a growth period from emergence to harvest (0 < development stage < 2) (Ma et al., ). Extinction coefficients for diffuse and direct visible light were used as the model default values, which were 0.60 and 0.75, respectively (Hassanli et al., ; Jiang et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…SWAP has performed well for simulations of farmland water and heat flow under different soil conditions (Martínez-Ferri, Muriel-Fernández, & Díaz, 2013). The SWAP model has also been used to schedule irrigation (Jiang, Feng, Ma, Huo, & Zhang, 2016;Ma, Feng, & Song, 2015;Rallo, Agnese, Minacapilli, & Provenzano, 2012) and estimate crop yield at the field and regional scale (de Jong van Lier, Wendroth, & van Dam, 2015;Hassanli, Ebrahimian, Mohammadi, Rahimi, & Shokouhi, 2016;Mokhtari, Noory, & Vazifedoust, 2018). Some research has shown that SWAP simulation results are superior to other models (Bonfante et al, 2010;Eitzinger et al, 2004;Hassanli et al, 2016).…”
mentioning
confidence: 99%
“…Precipitation, soil texture and water table depth jointly affected the amount of groundwater recharge and time lag between water input and groundwater recharge (Ma et al, 2015). We quantified some of these issues, but several items remain, such as the impact of rooting depth on crop yield and transpiration.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the many factors that affect the groundwater regime, it is difficult to quantify the contribution of each factor to changes in the groundwater table (Ma et al, 2016). To date, studies have discussed the influence of irrigation development on groundwater depletion (Hu, Delgado, Zhang, & Ma, 2005;Lv et al, 2013;Ma et al, 2016;Yang, Watanabe, Sakura, Tang, & Seiji, 2002) and the impact of implementing water-saving irrigation on halting the fall of the groundwater table or even raising the groundwater table (Liu et al, 2007;Hu et al, 2010, Ma, Feng, & Song, 2015. Unfortunately, the majority of existing studies have focused only on one irrigation district or several representative sites to explain and quantify the influence, and a regional-scale analysis has not been done.…”
Section: Introductionmentioning
confidence: 97%